Islamic Prudential Banking Concept to Reduce Non Performing Financing: Literature Review - Binti Nur Asiyah; M. Ridlwan Nasir; Muhamad Ahsan (Ekonomi Syariah IAIN Kudus, 2019)
Purpose - This paper aims to develop the concept of prudential banking based on sharia principles to minimize non-performing financing in Indonesia. Methode - This desk research was based on many relevant studies advanced in the literature. The review was particularly focus on Sharia Banking Law, Indonesian Banking Regulations, and Financial Services Authority Regulations. A secondary data published by the Indonesian Central Bank on Sharia Banking Statistics for 2014-2018 was used to sharpen the analysis. In addition, many previous studies on Sharia Banking conducted in other countries (e.g. Malaysia, Pakistan and other European countries) were discussed in order to widen the importance of Sharia banking in those countries. Findings - The findings of this study include as follows. First, the development of the concept of Islamic prudential banking in the operations of Islamic banks need to give attention towards business risk and the certainty of the implementation of Islamic principles. Second, the operational of Islamic banks need to consider the important of sharia human resources, sharia product, sharia process (marketing, management, and standard operational procedure (SOP)) as well. Research limitation- This research limitation article requires follow-up to explore the potential of applying Islamic prudential banking in depth to Islamic banks in Indonesia and apply it to every operational standard procedure from banks. Practical implications – The Practical implication is that Islamic prudential banking should be implemented in accordance with the Islamic concept in its operations so that it is truly able to minimize non performing financing. This study can also be used for policy instruments to improve Islamic Prudential Banking in Indonesia which is not yet available. Also, it can be implemented by other stakeholders of Islamic Banking . Social implication- The social implication of this study to increase work motivation and raises honesty in work, in accordance with the objectives of Islamic banks. Originality/Value - The originality of this study is due to the facts that studies on Islamic Prudential Banking have little examination. For this reason, this review study can be used as the important input to develop Islamic prudential banking and to be implemented by the banking and the regulators